Eosinophilic esophagitis - Where are we today? - Cristina Targa Ferreira; Mario Cesar Vieira; Glenn T. Furuta; Fernando Celso Lopes Fernandes de Barros; Mirna Chehade (Brazilian Society of Pediatrics, 2019)
Objective: The objective of this review is to provide an overview of the practical diagnostic and therapeutic approaches to eosinophilic esophagitis and to increase the visibility of the disease among pediatricians. Sources: A search of the MEDLINE, Embase, and CINAHL databases and recent consensus statements and guidelines were performed. Summary of the findings: The definition of eosinophilic esophagitis is based on symptoms and histology. It is important to rule out other diseases associated with esophageal eosinophil‐predominant inflammation. It is not yet clear whether the increased prevalence is due to a real increase in incidence or a result of increased awareness of the disease. Various options for management have been used in pediatric patients, including proton pump inhibitors, dietary restriction therapies, swallowed topical steroids, and endoscopic dilations. More recently, proton pump inhibitor‐responsive esophageal eosinophilia and eosinophilic esophagitis have been contemplated on the same spectrum, and proton pump inhibitors should be considered the initial step in the treatment of these patients. Conclusions: Eosinophilic esophagitis is a relatively new disease with a remarkable progression of its incidence and prevalence in the past two to three decades, and diagnostic criteria that are constantly evolving. It is important to better understand the pathogenesis of the disease, the predisposing factors, the natural history, and the categorization of varying phenotypes to develop diagnostic and therapeutic strategies that meet the clinical needs of patients. Resumo: Objetivo: Fornecer uma visão geral do diagnóstico e do tratamento da esofagite eosinofílica na prática clínica e aumentar a visibilidade da doença entre os pediatras. Fontes dos dados: Foi feita uma busca na literatura relevante nos bancos de dados Medline, Embase, CINAHL e consensos e diretrizes recentes foram revisados. Síntese dos dados: A definição de esofagite eosinofílica é baseada nos sintomas e na histologia. É importante excluir outras doenças associadas com inflamação esofágica predominantemente eosinofílica. Ainda não está claro se o aumento na prevalência é devido a um real aumento da incidência ou se é o resultado da maior suspeição diagnóstica. Várias opções para tratamento, inclusive inibidores de bomba de prótons, restrições dietéticas, esteroides tópicos deglutidos e dilatações endoscópicas têm sido usadas em pacientes pediátricos. Mais recentemente a eosinofilia esofágica responsiva a inibidores de bomba de prótons e a esofagite eosinofílica têm sido contempladas no mesmo espectro e os inibidores de bomba de prótons devem ser considerados como opção inicial no tratamento desses pacientes. Conclusões: A esofagite eosinofílica é uma doença relativamente nova com uma notável progressão da incidência e prevalência nas últimas 2‐3 décadas e critérios diagnósticos estão em evolução constante. É importante entender melhor a patogênese dessa doença, os fatores predisponentes, a história natural e a categorização dos diferentes fenótipos para desenvolver estratégias diagnósticas e terapêuticas que vão ao encontro das necessidades clínicas dos pacientes. Keywords: Eosinophilic esophagitis, Esophageal eosinophilia, Eosinophilic, Proton pump inhibitors, Palavras‐chave: Esofagite eosinofílica, Eosinofilia esofágica, Eosinofílico, Inibidores de bomba de prótons